The solution of nonlinear parabolic equation using variational iteration method - wartono wartono; Irma Suryani (Jurnal Matematika, Statistika dan Komputasi, 2020)
Variational iteration method is a semi analytic solution used to solve   the parabolic differential  equation both of homogen or nonhomogen. In the process of determining an approximation solution, this method did not use a linearization and a small pertubation. In this paper, the variational iteration method is implemented in the parabolic differential equation  in the form of  ut = uxx + f(u) + g(x, t) with appropriate intial condition. Furthermore, some examples of special parabolic differential equations are given to test the reliability and convergence of the method. Based on the result of study shows that the variational iteration method is  able to solve the parabolic differential equation with a good accuration.